Pengembangan Media Pembelajaran Video Animasi Stop Motion Dalam Menanamkan Sikap Anti Narkoba Di Sekolah Dasar - Riski Ananda; Tita Mulyati; Yayang Furi Furnamasari (Pusat Riset dan Inovasi Nasional, 2023)
This study was motivated by the lack of use of digital-based learning media in the learning process, the absence of counseling and guidance on the dangers of drugs in SDN Kalibaru 07 morning, as well as environmental factors around the school, namely Kalibaru Barat village, which is an area prone to drug abuse. To overcome these problems, efforts are needed to develop stop-motion animation video media that aim to produce stop-motion animation videos that are practical and effective. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The analysis phase includes an analysis of Learning media development needs and the characteristics of learners. The design phase includes the design of the GBPM and storyboard as a reference in developing stop-motion animation video media. The development phase includes product development and validity tests by experts, namely material experts with an average percentage score of 96.42% in the category